ANALISIS PENGARUH ORIENTASI PEMBELAJARAN TERHADAP KINERJA TENAGA PENJUAL MELALUI KERJA CERDAS, KEMAMPUAN JUAL, DAN PENJUALAN ADAPTIF SEBAGAI VARIABEL INTERVENING (Studi Kasus Tenaga Penjual Sepeda Motor Jepang di Magelang) - Putra, Randy Mahendra; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2018)
Salesperson is one of the important elements that contribute greatly to the company's profits. In addition, the salesperson is a party that deals directly with consumers so that it can influence the purchase decision. Therefore it is often referred to as the spearhead of the company. The high or low performance of salespeople is caused by various factors. One of the things that affect is the orientation of learning from self-salespeople. This study aims to analyze the effect of learning orientation on the performance of salespeople. Smart work, selling skills, and adaptive sales are used as intervening variables. The object of this research is the salespeople from Japanese motorcycles in Magelang. The sampling technique is purposive sampling, where the sample used is the salesman from the Japanese motorcycle that has been working for at least 6 months. Analytical technique using Structural Equation Model (SEM) - AMOS. Overall the results of this study showed that the orientation of learning has a positive effect on smart working, selling ability, and adaptive selling, smart working has a positive effect on the salesperson's performance, adaptive selling have a positive effect on salesperson performance, and selling ability negatively and insignificant to performance of salespeople.